Trends in mortality rates in female genital organs and breast cancers in Hungary between 1979 and 2013. (November 2015) - Hartai, Margit; Nyári, Tibor András; McNally, Richard J.Q.
Abstract: Objective: This study investigated annual and seasonal trends in deaths for cancers of the female genital organs and breast in Hungary between 1979 and 2013. Study design: Data on the numbers of cancer deaths were obtained from the published nationwide population register. Joinpoint regression was applied to investigate the yearly trends in cancer mortality rates. Cyclic trends were investigated using logistic regression, Edwards' and Walter-Elwood methods. Results: The majority of deaths from cancers of the female genital organs and breast occurred in winter but using the observed numbers of deaths a significant seasonal pattern was only revealed for deaths from breast cancer with a peak in January and a nadir in July. However, seasonality in the proportion of deaths from female genital organs and breast cancers out of deaths from all causes detected a different peak and nadir. The proportion of female genital organs and breast cancer deaths out of deaths from all causes was higher around the end of summer and significant seasonal variation with a peak in August and nadir in February was revealed. Conclusion: This Hungarian study suggests that there was a significant seasonal effect on female genital organs and breast cancer mortality. Both seasonal patterns are interesting and informative to potentiate prevention. Our findings suggest that infectious diseases may increase the risk of the mortality among the immune deficient patents.